Leonardo da Vinci: Et utrykt essay af Sophus Claussen - Barnwell, Jeppe (Danske Studier, 2020)
This paper presents a hitherto unpublished essay by the Danish symbolist poet Sophus Claussen (1865-1931). The essay entitled ‘Leonardo da Vinci’ was intended for the collection Løvetandsfnug (‘dandelion fluff’), 1918, but was for unknown reasons omitted in the final edition. In the essay, Claussen recalls when, at the Uffizi Gallery in Florence in 1902–03, he saw a painting (perhaps by Leonardo da Vinci) depicting the Annunciation to the Blessed Virgin Mary. At the time, the Virgin Mary of the painting reminded Claussen of a young Danish girl with whom he had been hopelessly in love some ten years prior. The remembrance of this past experience, at the time of writing the essay in early or mid 1918, causes him to contemplate not only the artistic method of Leonardo, but also, more generally, the relationship between chastity and lust, nature and imitation, and art and science. ‘Leonardo da Vinci’ has never been described in the secondary sources on Claussen’s work. It is, however, arguably both interesting and exemplary for its dual role as both a biographical and poetological lead in his essays and in his oeuvre as a whole.